Effects of permeable plugs on wellbore strengthening. (August 2020) - Liu, Yang; Ma, Tianshou; Chen, Ping; Wu, Bisheng; Zhang, Xi; Wu, Bailin
Abstract: Wellbore strengthening (WBS) treatment uses lost circulation materials (LCMs) to seal fractures emanated from a wellbore to enhance the pressure-bearing capability of a fractured rock formation during drilling a well. The plugging zone made of LCMs to prevent high wellbore pressure from being completely transferred to fracture tip is permeable and movable. The mechanical responses of wellbore-fracture-plug systems are thus important to WBS designs. A fully coupled hydraulic fracture model is presented to simulate the evolution of near-wellbore stress, fracture opening and internal pressure for finding the way of mitigating the risk of plug failure. Laboratory results were first reported on the ranges of plug permeability and strength in producing plug failure. A symmetric bi-wing fracture geometry is employed in the model, and the roles of in situ stresses, and plug location, dimension and permeability are studied in terms of dimensionless parameters. The numerical results show that in addition to increasing hoop stress, the less permeable plug can slow pressure enhancement rate at its downstream to postpone tensile plug failure caused by increasing fracture opening. The strengthening duration prolongs in rocks under an isotropic in situ stress condition, by plugging fractures at or near their fracture mouth, moderately increasing plug length and width, and decreasing plug permeability. Not only do the time-varying results recover most of the findings obtained by the fixed pressure fracture model, but they are more suitable to the plug failure analysis because the unbalanced pressure on both sides of the permeable plug, controlling shear plug failure, varies transiently. Highlights: A fully coupled hydraulic fracture model that considers plug permeability is developed for wellbore strengthening (WBS). The transient responses in pressure changes are important to plug failure analysis. The controlling parameters for time-varying responses are derived by scaling. The tensile and shear plug failure modes co-exist during WBS and the transient analysis determines which mode occurs first.